Improvement of the conventional preparation methods in Co/BEA zeolites: Characterization and ethane ammoxidation - Essid, Safaa; Ayari, Faouzi; Bulánek, Roman; Vaculík, Jan; Mhamdi, Mourad; Delahay, Gerard; Ghorbel, Abdelhamid (Elsevier Science BV, 2019)
Ethane ammoxidation into acetonitrile (AN) was successfully catalyzed by Co/BEA solids issued from improved preparation methods. The catalyst issued from the impregnation of [Co(NH3)(6)](2+) complex into BEA zeolite is very active in ethane ammoxidation (48% of ethane conversion and 90% of selectivity towards AN at 450 degrees C). Over this solid, the combustion of hydrocarbon molecules into CO2 was inhibited since the inefficient oxidic species occupied hidden sites inside the zeolite host as demonstrated by the CO-TPR experiments. However, the exchange of [Co(OH2)(6)](2+) complex, accompanying the conventional impregnation and solid-state ion exchange, favoured the formation of Co3O4 oxide species, which restricted the ethane conversion into AN during ammoxidation. Nevertheless, the exchange of aqua complex in ammonia stream inhibited the formation of oxidic species and led to efficient ammoxidation catalysts. Meanwhile, ammonia favoured the formation of Co4N (detected by XRD, TPR and TPD) to the detriment of bare Co2+ ions. In this context, very low amounts (similar to 0.05 mmol g(-1)) of bare Co2+ ions, sited in the beta-sites, are sufficient to catalyze ammoxidation at 450 degrees C. However, beside their amount, the stability of these ions is a crucial parameter to be considered and studied by FTIR upon CO adsorption at -196 degrees C.
Zlepšení konvenčních metod přípravy Co/BEA zeolitů: Charakterizace a amoxidace etanu.
Keywords: Ammoxidation; Impregnation; Solid-state ion exchange; Cobalt complexes; amoxidace; impregnace; iontová výměna; Co komplexy